Maxillofacial Injuries: A Retrospective Study of 576 Cases - Srivastava, Dhirendra; Srivastava, J. L. (Indian Journal of Plastic Surgery, 1989)
The present study is a retrospective analysis of 576 cases of facial fractures involving Mandible, Middle third and the Zygomatic complex. The high incidence of Road Traffic Accident has been the commonest case of facial fractures in the present series.
Keywords: R. T. A. (Road Traffic Accident); Maxillofacial; LeFort; Zygomatic Complex; M/3-Middle Third